Fundamental concepts: The solution to contemporary management problems – A sine qua non or non sequitur? - K. K. Naidoo (South African Journal of Business Management, 2004)
The last quarter of the 20th century, particularly the last decade - with the advent of more sophisticated technology, rising educational levels amongst workers and globalisation - saw the arrival of a plethora of management tools and theories; and notwithstanding the sometimes their contradictory nature; an even stronger and louder message being spread viz. that management in the 21st century would have a different face from that worn in the 20th century. This paper raises various questions: Is contemporary management theory nothing more than an accumulation of contradictory fads? Can universal management principles be extracted from the accumulated mass of information? Do the classical writers have words of wisdom to impart to the manager of the 21st century? In so doing, this paper traces a trajectory of management thought by examining the place of the seminal work of Chester I Barnard of the classical school of thought, in the light of contemporary trends and problems; and debates the currency of fundamental management principles.
Keywords: 650